Spiritualitas Musik Hazrat Inayat Khan Dalam Perspektif Estetika Pada Pandangan Seniman Teater Awal Bandung - Aqmaldy Noer Firdausya (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This study aims to determine the spirituality of Hazrat Inayat Khan's music from an aesthetic perspective, as well as the views of the artists of Teater Awal Bandung towards it. This research method uses a qualitative approach with library research sources plus field observations through interviews with the artists of the Teater Awal Bandung related to Hazrat Inayat Khan's thoughts on music. The results of the study found that the spiritual and aesthetic dimensions of Hazrat Inayat Khan's music are related to each other even though they are not identical. The source of beauty comes from God who moves humans through a fundamental element called love. The artists of the Teater Awal Bandung agreed that every universe and everything in it is a harmony that has a tone and gives birth to beautiful music, music is also able to give peace of mind and become a means of meditation for humans to know God.